Magnitude of Dental Caries and Its Associated Factors Among Governmental Primary School Children in Debre Berhan Town, North-East Ethiopia - Aynalem YA; Alamirew G; Shiferaw WS (Dove Medical Press, 2020)
Yared Asmare Aynalem,1 Getu Alamirew,1,2 Wondimeneh Shibabaw Shiferaw1 1Department of Nursing, College of Health Science, Debre Berhan University, Debre Berhan, Ethiopia; 2Debre Berhan Referral Hospital, Debre Berhan, EthiopiaCorrespondence: Yared Asmare AynalemDepartment of Nursing, College of Health Science, Debre Berhan University, P.O. Box 445, Debre Berhan, EthiopiaEmail yaredasmare123@gmail.comBackground: In Ethiopia, oral health prevention and treatment have gotten low attention in the government, and the existing dental services are privately owned and thus expensive. Hence, this study aimed to assess the prevalence of dental caries and its associated factors among governmental primary school children in Debre Berhan town, Ethiopia, 2019.Methods: An institutional-based cross-sectional study was conducted from January 30 to February 14/2019. A total of 417 primary school children were selected using computer-generated simple random sampling and interviewed using structured and pretested questionnaires. Data were coded, entered, and cleaned using Epi-data version 3.1 and export to SPSS version 22 for analysis. Binary logistic regression analysis was employed to test the association between dependent and independent variables. P-value less than 0.05 was taken as significant association. Finally, the result of this study was present by text, tables, and graphs.Results: Out of the 396 study participants, 135 (34.1%) had dental caries. Of these, more than half, 95 (59.37%) had the pre-molar decayed. Two hundred eighty-five (72.0%) of them were cleaned their teeth. The Independent predictors of dental caries were drinking sugared tea [AOR= 2.034, 95% CI: (1.223– 3.385)] and food particle on their teeth [AOR= 6.709, 95% CI: (3.475– 12.954)], which had shown a significant association with dental caries.Conclusion: The over magnitude of dental caries was relatively high and found to be a public health problem. Drinking sugar tea, presence of food particles, or dental plaque were significantly associated with dental caries. In contrast, merchant occupation reduced the chance of dental caries. Giving health education to minimize drinking sugar tea and cleaning their teeth after consumption of sugar tea should be given attention.Keywords: dental caries, children, associated factors, Ethiopia